SOCIAL MEDIA AS STRATEGY TO IMPROVE STUDENTS’ PARTICIPATION AND MOTIVATION IN ENGLISH SUBJECT - Nafisah Endahati; Rudha Widagsa (Elite : English and Literature Journal, 2018)
The objective of this study is to test the learning model of blended learning by using social media as the learning tool to improve students’ participation and motivation in English subject. The study helps to solve problem of learning time restrictiveness by wielding students’ familiarity with internet technology used outside the classroom. The study implemented quasi-experiment to collect the data by using test and questionnaire. The respondents were students Elementary School Teacher Study Program of University of PGRI Yogyakarta. There were 70 students who were divided into two classes. A class was conducted as control group, while the other one was the experimental group. In the control group, English subject was taught by implementing conventional class model. The students in the experimental group were taught by blended learning which were the combination of classical and online models through social media. Social media used in this study were ones which supported learning process as sharing audio, video, as well as other online media. The writer chose Facebook as the media learning because all respondents used such kind of social media. The integration of social media as the effort to improve students’ participation and motivation remain successful. The general discussion is on the implementation of e-learning platform in learning process. According to survey, students were interested more in using social media compared with e-learning platform. The result of the study proved that English learning process by using blended learning method with social media helped students’ participation and motivation. The posttest result of the experiment class was better than the control class.